Lakshadweep High Propagation and Impacts on the Somali Current and Eddies During the Southwest Monsoon - Ernst, Paul A.; Subrahmanyam, Bulusu; Trott, Corinne B. (Scholar Commons, 2022)
Climatological eddies in the Arabian Sea (AS), including the Lakshadweep High (LH) and the Great Whirl (GW), play major roles in the regional fluxes of upper ocean properties. For the first time, we apply an eddy tracking algorithm to the LH using altimetric sea surface height observations from 1993 through 2019. We additionally analyze the LH's water mass composition throughout its life cycle using the 1/12° Global eddy resolving physical ocean and sea ice reanalysis (GLORYS12). We observe that the second annual downwelling coastal Kelvin wave's (CKW) arrival during the winter monsoon is primarily responsible for generating the LH. In March, Rossby waves propagate along 8°N at the same speed of that of the LH. In 17 of 27 years, the LH maintains coherence across the AS. The LH sustains a shallow lens of lower salinity Bay of Bengal water up to 68°E in these years. In the remaining 10 years, the LH dissipates between 60°E and 70°E or fails to propagate beyond the southwest Indian coast. We attribute the differences between propagation types to fluctuations in the CKW strength, differences in wind stress between the southern tip of India and Sri Lanka, and the variable distribution of wind stress curl around the LH. We also find that longer propagating LH types negatively correlate with the eddy kinetic energy of the Somali Current region during the summer monsoon. We conclude that, upon its arrival in late July, the LH either merges with or replaces the GW, disrupting the cyclone that normally orbits the GW.